Why you should Mini-Med School: Mini-Med School as an intervention to increase health literacy - Shatenko, Sergiy; Harder, Samuel; Gair, Jane (Canadian Medical Education Journal, 2020)
Background: Health literacy is an increasingly important topic in healthcare given that low health literacy is widely prevalent and linked to poorer health outcomes and higher healthcare costs. We sought to determine if a Mini-Med School delivered by medical students could prove to be an effective intervention to improve health literacy in the elderly. Methods: This study took place in the context of the University of British Columbia Medical Doctorate Undergraduate Program’s Flexible and Enhanced Learning course. It aimed to evaluate the effectiveness of a Mini-Med School lecture series as an intervention to increase health literacy in 24 volunteer participants from the University of Victoria Retirees Association. This was a cross sectional study comparing health literacy pre- and post-intervention using the validated Health Literacy Questionnaire. Results: There was a statistically significant improvement in 7 of 9 scales of health literacy when participants repeated the Health Literacy Questionnaire 6 weeks post-intervention as well as positive outcomes from both a student learning and community outreach perspective. Discussion: This study demonstrates that a Mini-Med School program is an effective way to increase health literacy; adds to the minimal research surrounding Mini-Med Schools; and should further encourage Canadian medical schools to use Mini-Medical Schools as method of engagement and advocacy with their communities.